2020
DOI: 10.1111/codi.15037
|View full text |Cite
|
Sign up to set email alerts
|

A study investigating the perfusion of colorectal anastomoses using fluorescence angiography: results of the FLAG randomized trial

Abstract: Aim Our aim was to evaluate the efficacy of indocyanine green (ICG) fluorescence angiography (FA) in reducing the incidence of anastomotic leakage (AL) following colorectal anastomosis. Method A single-centre randomized trial was undertaken between 2018 and 2019. Those patients who underwent a stapled colorectal anastomosis were randomized 1:1 for ICG FA versus visual clinical assessment of blood perfusion of the anastomosed colon and rectal stump (non-ICG FA group). The primary endpoint was to assess whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
115
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(118 citation statements)
references
References 19 publications
1
115
0
2
Order By: Relevance
“…Traditional intra‐operative visual perfusion assessment has been shown to be suboptimal [3] and surgeons are looking to indocyanine green (ICG) fluorescence angiography as an adjunct to clinical judgement. A significant body of work demonstrated feasibility of use [4,5] and a recent randomized trial showed positive results [6] however, not all studies have found similarly [7]. Although clinical trials are ongoing, signal sensing and presentation have not been standardized.…”
mentioning
confidence: 99%
“…Traditional intra‐operative visual perfusion assessment has been shown to be suboptimal [3] and surgeons are looking to indocyanine green (ICG) fluorescence angiography as an adjunct to clinical judgement. A significant body of work demonstrated feasibility of use [4,5] and a recent randomized trial showed positive results [6] however, not all studies have found similarly [7]. Although clinical trials are ongoing, signal sensing and presentation have not been standardized.…”
mentioning
confidence: 99%
“…Some phase II trials con rmed the feasibility, low cost and high success rate of this procedure (14-17), reporting a leakage rate (< 3%) lower than expected on the basis of historical series, with particular reference to rectal anastomosis. Some randomized prospective controlled trials are going to be published (18), and some other efforts are nalized to a better understanding of dynamic information of perfusion (19).…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the publications were retrospective, there were 2 prospective studies 13,26 and 2 randomized controlled trials. 11,12 Among the retrospective studies, a number of authors attempted to perform a matched analysis using propensity-scoring. 23,25,27,28,37 We identified only 1 trial which had ongoing recruitment on clinicaltrials.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Nine studies evaluated the use of ICG FA in a combination of patients undergoing both colon and rectal surgery. 11e13,23,25,29,32,33,39 Although the majority of studies adopted a laparoscopic approach, some studies included a combination of laparoscopic and open approaches, 11,13,23,25,32 whereas others included robotic-assisted surgery, 13,24,26,31 and 1 evaluated the use of ICG FA in transanal, total mesorectal excision. 35 There was also variability regarding the definition of anastomotic leakage.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation